(untitled) (Global Journal of Human-Social Science, 2020)
The Ombudsman or Public Complaints Commission which came up in the 19th century is a body established by law to address administrative radicalism and injustice in public institutions. This body was of boisterous use in the Scandinavian countries in Europe to address administrative injustices without resorting to courts of law. In Britain, it is called Parliamentary Commissioner. In Russia, it is called Prosecutor General, and in Nigeria, it was introduced in 1975 as Public Complaints Commission and attached to the legislature as the supervising agency. This body is recognized by the 1999 Constitution of Nigeria but its performance appears to be unnoticed because of certain bottlenecks. This paper intends to highlight these gridlocks which include incapacity to give effect to its decisions, financial incapacity and other administrative setbacks. It is our belief that if these bottlenecks are removed the Ombudsman will perform in Nigeria as in other countries where it has favourable conditions.